(untitled) (Revista Nacional de Odontología, 2025)
The occurrence of osteonecrosis of the jaws has been observed in individuals who take bisphosphonates and have undergone surgical procedures involving the teeth and alveolar bone. The use of bisphosphonates in combination with dental implants is a common treatment approach in the adult population. The aim of this literature review is to analyze and synthesize the scientific evidence from 50 articles related to successful and unsuccessful outcomes of dental implant placement in patients receiving oral or intravenous bisphosphonate therapy. This was achieved by searching, selecting, and analyzing the identified articles to identify patterns, determining factors, and lessons learned from the success and failure cases reported in the scientific literature. A literature search was conducted using the PubMed database, including studies, data, and articles directly related to dental implants and bisphosphonates. Relevant data, such as sample size, main results, and conclusions, were extracted from the articles and analyzed and synthesized using comparative tables to identify trends and differences in the effects of bisphosphonates on implant osseointegration and the observed complications. In conclusion, the comparison of the 50 articles on dental implants and bisphosphonate use reveals that this therapeutic combination can lead to complications, particularly osteonecrosis of the jaws. Approximately 10% of patients treated with dental implants experience complications that can lead to treatment failure.